Pest Attack on Eucalyptus alba in Gunung Nona Protected Forest Area, Ambon City - Fransina S. Latumahina; Mohamad Lihawa (Agrologia, 2020)
Eucalyptus (Eucalyptus alba) in Gunung Nona protected -forest play important roles as protective plants of erosion and flooding that often occurs in the region. However, in the last decade, the existence of the Ekaliptus stand has been under pressure due to pests with high levels of damage reducing forest cover. The study was conducted to determine the type of pests, the intensity of damage and the extent of pest attack in the Eucalyptusalba in Gunung Nona Forest. The study method was survey with10% of 20 sample trees sampling intensity. Observations on tree-level Eucalyptus stands were conducted from roots to leaves by looking at the symptoms and signs of pest attacks. The research found three types of pests, namely Ulat Grayak (Grayak Caterpillars). The highest intensity of damage is 72,37%  due to pest attacks by Spodoptera sp, 19,22% or moderate criteria by Hyposidra talacaand and 7.09% or mild criteria by Macrotermes Gilvus Hagen. While the extent of pest attack are 67,7% by Spodoptera Sp, 40,9% by Hyposidra talaca, and  15,9% by Macrotermes gilvus Hagen which is classified as strict, medium, and  mild criteria, respectivelly.